PENYULUHAN TENTANG TRANSFORMASI LAYANAN PERPUSTAKAAN BERBASIS INKLUSI SOSIAL DI PERPUSTAKAAN DESA DEMANGREJO KULON PROGO - Ernawati; Irpina, Wiwin; Mursyid, Moh; Syahida, Khoirun Nisa (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2024)
Abstract Libraries as one of the centers and providers of information for the community, along with the current development of technological and information advances, libraries must also be able to adapt to existing advances. The National Library of the Republic of Indonesia as the main library in Indonesia has promoted the transformation of library services based on social inclusion. The Village Library is a type of public library as a center that provides information for all communities fairly for learning and lifelong activities. The public can be directly involved in library activities. However, the Demangrejo village library is currently unable to provide innovation services for its community, so the library is still empty of visitors. Therefore, outreach activities are needed regarding the Transformation of Library Services Based on Social Inclusion. The aim of this community service is to improve excellent library services, increase user visits and the community's reading and writing culture and improve the community's economic welfare. The methods used in this outreach activity are material development, questions and answers and implementation of outreach and evaluation. The results of the outreach activities showed that participants already knew and understood the transformation of library services based on social inclusion. In this way, community service activities through counseling provide benefits for village libraries and their managers because they can increase new knowledge and in-depth understanding of social inclusion-based library services. Keywords: Transformation, Library Services, Social Inclusion